An ultra-low-voltage VCO-based ΔΣ modulator using self-compensated current reference for variation tolerance - Narasimman, Neelakantan (2021)
This paper introduces a voltage-controlled-oscillator-based (VCO-based) first-order delta-sigma (ΔΣ) modulator that uses a novel current reference to improve the robustness of the modulator at ultra-low operating voltages. The proposed current reference harnesses the difference in transistor characteristics between weak inversion and moderate inversion to generate residue voltage, which is a function of process and temperature variations. The current generated by the proposed reference is used to bias a fully differential VCO integrator and a feedback current digital-to-analog conversion in the delta-sigma modulator for variation tolerance. Test chips designed and fabricated in 65-nm CMOS technology operate successfully at 0.3 V and achieve SNDR of 56.1 dB across 10 kHz bandwidth while consuming only 510 nW of power. This corresponds to a state-of-the-art figure of merit of 49 fJ/conv.-step. Measurement results for the proposed current reference and the modulator also demonstrate 3 × and 20 × improvement in process and temperature variation tolerance, respectively, while operating at such low voltages.